2015
DOI: 10.1590/0100-83582015000200006
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Genetic Structure in Populations of Arrabidaea bilabiata (Sprague) Sandwith in the Amazonas State

Abstract: -Weeds in pastures can intoxicate animals, and Arrabidaea bilabiata is the most important species for herbivores in floodplain areas in the Amazon Basin. Genetic diversity studies in natural populations may contribute to the better understanding of the range of toxicity and the genetic variability organization in this species. The objective of this study was to assess the variability and genetic structure in six populations of A. bilabiata sampled in floodplain areas in three municipalities of the Amazonas Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(32 reference statements)
1
0
0
Order By: Relevance
“…Since the breeding system is affected by genetic and environmental factors, a genetic variation among the seeds of a plant is the norm, especially in allogamous species. In our study, a considerable genetic diversity was observed within the families (especially 1 and 21), and estimated values are comparable to those found in small populations of another forest climber: Arrabidaea bilabiata (Souza et al 2015).…”
Section: Resultssupporting
confidence: 88%
“…Since the breeding system is affected by genetic and environmental factors, a genetic variation among the seeds of a plant is the norm, especially in allogamous species. In our study, a considerable genetic diversity was observed within the families (especially 1 and 21), and estimated values are comparable to those found in small populations of another forest climber: Arrabidaea bilabiata (Souza et al 2015).…”
Section: Resultssupporting
confidence: 88%